Efficacy of mirror therapy in subacute stroke: A case-control study - Deo Rishi Tripathi; Mahesh Kumar Talele; Surya Bhan Singh; Shipra Chaudhary; Amod Kumar (Al Ameen Medical College, 2016)
Context: The effect of mirror visual illusions on brain activity has been investigated in a number of studies. Motor imagery can be defined as the covert cognitive process of imagining a movement of your own body (-part) without actually moving that body (-part). Aims: Our aim was to investigate whether mirror therapy is effective at short-term (at 4wk) and long-term (at 6month) intervals on motor recovery, spasticity, and hand-related functioning of patients with subacute stroke. Methods and Material: The study recruited 40 patients suffering from sub-acute stroke with a male: female ratio of 27:8 of mean age 48.42years (age range 23-70 years). Mirror therapy was given in OPD setting over 5 weekly doses. Both the mirror group and control group participated in a conventional stroke rehabilitation program, 6 days a week, 2 to 3 hours a day with therapist in hospital and 1 hour at home for 4 weeks and follow-up at 6 months . The conventional program consists of neuro-developmental facilitation techniques, physiotherapy, occupational therapy, and speech therapy (if needed). For the same period, the mirror group received an additional 30 minutes of mirror therapy program per day. Statistical analysis used. Results: The mirror therapy treatment compared to the control group showed significant improvement at 4 weeks re-assessment from baseline assessment on hand functioning in Brunnstorm, Action Research Arm test and Functional Independence Measures. The mirror therapy treatment compared to the control group at 6-months of follow up reassessment from 4 weeks assessment showed moderate but insignificant improvement in the Brunnstorm and Action Research Arm test and significant improvement in Functional Independence Measures. Conclusion: In our group of subacute stroke patients, hand function improved more after mirror therapy in addition to a conventional rehabilitation program compared with a control treatment directly after 4 weeks of treatment and at the 6-month follow-up, whereas mirror therapy does not affect spasticity.